Med en enad syn på rehabilitering - En studie av samverkan inom arbetslivsinriktad rehabilitering - Allansson,Sofia (2013)
The following bachelor thesis investigates how successful the cooperation between Försäkringskassan and Arbetsförmedlingen is at a local level. These two authorities have a joint mission since February 2012 to help people, who are about to be unqualified for compensation through their health insurance, to find a job through rehabilitation. Through the theoretical approach joined-up government, I have found that despite some minor issues it is possible to qualify their aim of cooperation as a success. Through their united purpose around rehabilitation they have found a way to work together and to separate their differences. One of the greatest factors that have affected the outcome is a good leadership and also a clearly defined purpose. The fact that they have well adopted an “adopt, adapt, act” has also lead to a well-developed organisation. A few issues could still be spotted, with inadequate evaluation systems and a lack of formal guidelines. The conclusion drawn from this study is that they have managed to develop a stable foundation for a continued joint-approach. To reaffirm that it is sustainable, it is necessary to look upon some issues and to proceed with continuous evaluations in the future.
Keywords: samverkan; Försäkringskassan; Arbetsförmedlingen; Joined-up Government; förstärkt samarbete; arbetslivsinriktad rehabilitering; svensk förvaltning